A critical review of the digital and green twin transitions: Implications, synergies and trade-offs - Rafael Mu\~noz de Bustillo Llorente (European Commission, Joint Research Centre (JRC), 2024)
The working paper explores the complex relationship between the digital and green transitions and analyses how these two transformations, although independent, influence each other. It discusses the potential positive effects of digitalisation in the fight against climate change, such as improved efficiency and coordination of production and the dematerialisation of goods and services. However, the paper also highlights the risk of significant backlash due to the existence of rebound effects, as well as the potential negative consequences of digitalisation for the environment, including the high-energy consumption associated with digital technologies, the generation of e-waste, and the environmental impact of cryptocurrencies and artificial intelligence. Finally, the paper analyses the current state of adoption of the two transitions in companies, showing that although digitisation is more common, a significant percentage of companies are implementing both transitions, especially among large companies.
Keywords: 330; Twin transitions; Digital Transition; Energy Transition; e-waste